Leaching systematics and matrix elimination for the determination of high-precision Pb isotope compositions of ocean island basalts - Silva, I; Weis, D; Barling, J; Scoates, J (2009)
Ocean island basalts from Hawaii and Kerguelen were analyzed for their Pb isotopic compositions to assess the effect of acid leaching and matrix elimination by Pb anion exchange columns on reproducibility and accuracy. Unleached samples consistently yield Pb isotopic ratios that reflect the incorporation of foreign material. Leaching removes up to 70-80% of the total Pb content of the samples with corresponding weight losses between 35 and 60%. The older and more altered Kerguelen basalts show better external reproducibility than the Hawaiian basalts, which appears to be due to the presence in the Hawaiian samples of more radiogenic contaminants (e.g., seawater Pb, drilling mud, and related alteration phases). All leached samples purified twice on anion exchange columns show more radiogenic Pb isotopic ratios than those processed once. The difference is larger for tholeiitic basalts (Hawaiian and Kerguelen Plateau) than for transitional to alkalic basalts (Kerguelen Archipelago). The small differences in measured ratios of total procedural triplicates reflect differential elimination of residual alteration via leaching and matrix effects. The effectiveness of matrix elimination depends on the specific basalt composition, and tholeiitic basalts (i.e., low Pb concentrations) require two passes on anion exchange columns. This study shows that all steps in sample processing are critical for achieving accurate high-precision Pb isotopic compositions of ocean island basalts. © 2009 by the American Geophysical Union.